Global Outreach Programme 7.0 (UiTM-UM) in Malang, Indonesia: an unforgettable experience / Qasdina Amira Abd Rashid, Diyana Fatimah Badrulhissham and Siti Syaida Sirat - Abd Rashid, Qasdina Amira; Badrulhissham, Diyana Fatimah; Sirat, Siti Syaida (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2024)
Global Outreach Programme 7.0 (UiTM UM) (GOP 7.0 (UiTM-UM)) in Malang, Indonesia was one of the best experiences we had during our degree program at UiTM. This event was organized by the School of Chemistry and Environment, Kuala Pilah Campus and Department of Chemistry, Universitas Negeri Malang (UM). On the 25th of August, we departed from KLIA, Malaysia, and after a smooth 2- hour 40-minute flight, we landed at Juanda International Airport in Indonesia. Upon arrival, we were warmly welcomed by lecturers from UM, before embarking on a 2-hour bus ride to the university. As we set foot on the campus, we were immediately captivated by the beauty and grandeur of the buildings. We were accommodated at the university’s Asrama Edelweiss International.